Pengaruh Penggunaan Buku Ajar IPA Terpadu Kontekstual Tema Gelombang dalam Kehidupan Sehari-hari Terhadap Kompetensi IPA Siswa Kelas VIII SMPN 13 Padang - Rezki Putri; Asrizal Asrizal; Hidayati Hidayati (Universitas Negeri Padang, 2018)
The 2013 curriculum requires science learning in junior high schools to be implemented in an integrated manner and covers all aspects of competence, namely attitudes, knowledge, and skills. The facts of science learning applied in schools have not been integrated. One solution to this problem is to implement contextually integrated science textbooks. The purpose of this study was to determine the effect of integrated science books on the competence in class VIII SMPN 13 Padang. This type of research is quasi-experimental research with the design of the Postest only Non-Equivalent Control Group. The population of this study were eighth grade students of Padang State Junior High School 2017/2018 Academic Year, Sampling using purposive sampling technique. Instruments used, an observation sheet for attitude aspects, a written test for knowledge aspects and a performance assessment sheet for skills competency. The data obtained were analyzed using descriptive statistical analysis, and the average comparison test. Based on the results of the study, it can be concluded that the results of the study are the use of integrated science books on contextual textbooks in everyday life that have a significant influence on students' competencies for the three aspects of competence at 95% level confidence in class VIII SMPN 13 Padang.